Nepal : 2017 Article IV Consultation-Press Release; Staff Report. - International Monetary Fund. Asia and Pacific Dept. (Washington, D.C. : International Monetary Fund, 2017)
This 2017 Article IV Consultation highlights the rebound of Nepal's economy following a slowdown caused by the 2015 earthquakes and trade disruptions at the southern border. The growth of real GDP at market prices slowed to 0.6 percent in 2015/16 (mid-July 2015 to mid-July 2016). Due to trade disruption, shortages of fuel and other essential goods drove up inflation to 12 percent (year over year) in January 2016, but it eased subsequently to 3.2 percent in January 2017, mainly because of lower food prices. Growth is projected to reach 5.5 percent in 2016/17, and inflation is expected to undershoot the central bank's mid-2017 target of 7.5 percent.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet